Relationship Between Ankle-Brachial Index and Left Ventricle Ejection Fraction in Patients on Hemodialysis (Iranian Journal of Kidney Diseases, 2015)
Introduction. Ankle-brachial index (ABI) is a noninvasive test which employs as a diagnostic marker of atherosclerotic peripheral vascular disease in hemodialysis patients. This study aimed to investigate the association between ABI and left ventricular ejection fraction (LVEF) in patients on hemodialysis. Materials and Methods. Eighty-six patients with end-stage renal disease undergoing hemodialysis and 100 patients referred for echocardiography without apparent kidney disease were included. Ankle-brachial index was calculated by dividing the highest ankle pressure (the left and right dorsalis pedis and posterior tibial) by the brachial systolic blood pressure on the arm with no arteriovenous fistula. The relationship between ABI and LVEF was investigated. Results. The hemodialysis patients were older on average than the control group (P = .004). The total average of ABI in the hemodialysis group was less than 0.9 in 20 patients (23.3%) and 0.9 to 1.3 in 66 (76.7%). These were 11 (11%) and 89 (89%), respectively, among the controls (P = .02). The mean LVEF was 49.7 ± 8.6% in the hemodialysis patients and 53.8 ± 9.5% in the controls (P = .003). There was a significant correlation between LVEF and ABI in the hemodialysis patients (r = 0.06; P = .001), and ABI could predict the LVEF with sensitivity and specificity of 90% and 94.1%, respectively (positive predictive value, 34.6%; negative predictive value, 48.5%). Conclusions. These findings show that ABI may be applied in predicting the presence of left ventricular systolic dysfunction in hemodialysis patients. Further studies are recommended to confirm this association.